Distinct patterns of health risk behaviours in adolescents with thalassaemia - Pattaporn Kaewkong; Nonglak Boonchooduang; Narueporn Likhitweerawong; Pimlak Charoenkwan; Orawan Louthrenoo (Annals of Medicine)
Background Thalassaemia is a significant public health concern in Southeast Asia, yet little is known about health risk behaviours in adolescents with this condition. This study aimed to compare health risk behaviours between adolescents with thalassaemia and healthy controls, and to identify associated clinical and sociodemographic factors.Methods This cross-sectional study included 60 adolescents with thalassaemia (aged 10–18 years) and 60 age- and sex-matched healthy controls in Thailand. Health risk behaviours were assessed using the validated Thai Youth Risk Behaviour Survey. Clinical data were extracted from medical records. Multivariable logistic regression was used to identify factors associated with risk behaviours.Results Adolescents with thalassaemia reported higher rates of non-seatbelt use (25.0% vs. 1.7%, p < 0.001) and mental health problems (13.3% vs. 0.8%, p = 0.027) compared to controls. However, they exhibited lower rates of inadequate exercise (70.0% vs. 86.7%, p = 0.045) and excessive screen time (66.7% vs. 96.7%, p < 0.001). In the thalassaemia group, older age (aOR = 2.78, 95% CI: 1.09–7.09), female gender (aOR = 39.73, 95% CI: 0.89–1770.49) and lower pre-transfusion haemoglobin levels (aOR = 0.09, 95% CI: 0.01–0.64) were associated with increased odds of mental health problems. Higher pre-transfusion haemoglobin levels were associated with lower odds of violent behaviour (aOR = 0.44, 95% CI: 0.21–0.92).Conclusions Adolescents with thalassaemia exhibit distinct patterns of health risk behaviours, influenced by age, gender and disease severity. These findings underscore the need for integrated physical and psychosocial care, highlighting the importance of tailored health education and interventions for this vulnerable group.